Life and death in Rikers Island - Venters, Homer (Johns Hopkins University Press, 2019)
Dying in jail : Carlos Mercado and Angel Ramirez -- Injury and violence -- Solitary confinement -- Serious mental illness in jail -- Human rights and correctional health -- Race : Keleif Browder -- Sexual assault on Rikers : Maria and Brianna -- Correctional health -- Transparency and governance -- What to do with Rikers